A cross sectional study on the prevalence of diabetes mellitus among adult population in a peri-urban area of West Tripura, India - Tripura, Kaushik; Nag, Kaushik; Karmakar, Nabarun; Datta, Anjan; Bhattacharjee, Partha (International Journal of Research in Medical Sciences, 2019)
Background: Diabetes mellitus, a major lifestyle disease is undoubtedly the most challenging public health problem of 21st century with a worldwide prevalence of 387 million (8.3%). The objective of this study was to get an estimate of the prevalence of diabetes mellitus and associated factors in a sample of adult population in a peri-urban area of West Tripura. Methods: In a cross-sectional study, prevalence of diabetes mellitus was found among adult population of a peri-urban area (Dukli) of west Tripura from April 2016 to May 2016. Multistage random sampling was followed to include 76 participants. Taking house as a sampling unit, every 5th house was chosen for this study. From every selected house, one adult participant was chosen by simple random sampling until desired sample size was attained. Collected data was compiled and analyzed with the help of statistical package for social sciences (SPSS 16.0.). Chi-square, Fischer exact test was applied to find out association. Results: The mean age of the study participants was 42.21±17.65 years, comprised of 23.7% male and 76.3% female. The prevalence of diabetes mellitus was 17.1% among study participants. Diabetes was found highest in 39-58-year age group (37.5%). Males were more affected with diabetes mellitus (22.2%) compared to females (15.5%). The study also revealed a significant association of diabetes mellitus with family history of diabetes mellitus (p value 0.00). Conclusions: Present study showed very high prevalence of diabetes mellitus among adult population. Healthy lifestyle measures might reduce burden of diabetes mellitus which could be evaluated in future research.